End-to-end bandwidth estimation in TCP to improve wireless link utilization - S Mascolo; A Grieco; G Pau; M Gerla; C Casetti; et al. (European Wireless Conference, Florence, Italy, 2002)
TCP Westwood (TCPW) is a sender-side only modification of TCP Reno congestion control that exploits an end-to-end bandwidth estimation mechanism to set the values of Slow-Start-Threshold and Congestion-Window after a congestion episode, that is after three duplicate acknowledgments or a timeout. TCP Westwood represents an innovative variant of the AIMD mechanism that we call Additive Increase Adaptive Decrease (AIAD). The aim of this paper is to investigate TCP Westwood performances in the most common wireless scenarios. We will focus on utilization of wireless links by comparing Westwood vs Reno throughput. Moreover we study the friendliness between TCP Westwood and TCP Reno in wireless scenarios. Simulations and measurements show that Westwood utilizes wireless links much better than Reno. We choose three common scenarios including respectively a mobile client, a mobile server and a GEO satellite link. Simulation results show that Westwood obtains a remarkable throughput improvement up to 578% with respect to Reno over wireless links. Moreover, TCPW does not degrade TCP Reno performances. Finally, measurements carried out across a NASA high-sped network test-bed show an improvement of TCPW throughput up to 185% with respect to Reno.